Prevention of young infant infections using oral azithromycin in labour in Fiji (Bulabula MaPei): study protocol of a randomised control trial. Issue 12 (1st December 2022) - Hume-Nixon, Maeve; Ratu, Tupou; Clark, Stephanie; Nguyen, Cattram Duong; Neal, Eleanor F G; Pell, Casey L; Bright, Kathryn; Watts, Emma; Hart, John; Mulholland, Kim; Fong, James; Rafai, Eric; et al.
Abstract : Introduction: Infections are a leading cause of neonatal mortality globally and can be transmitted from mother-to-child vertically or horizontally. Fiji has higher rates of serious neonatal infections and infant skin and soft tissue infections (SSTIs) than high-income countries. Research from the Gambia found that a single dose of oral azithromycin in labour decreased bacterial carriage and infections in mothers and infants, particularly infant skin infections. The Bulabula MaPei clinical trial evaluates the safety and efficacy of a single dose of azithromycin in labour in reducing the incidence of maternal and infant SSTIs and other infections and the impact on bacterial carriage. It will also describe the effect of azithromycin on antimicrobial (AMR) resistance, the maternal and infant microbiome, and infant dysbiosis. Methods and analysis: We are conducting a blinded, placebo-controlled randomised clinical trial administering 2 g of oral azithromycin, or placebo, given to healthy, pregnant women (≥18 years) in labour in Suva, Fiji. The primary outcome is the cumulative incidence of SSTIs in infants by 3 months of age. Secondary outcomes include the incidence of other infant and maternal infections, and safety and tolerability of azithromycin in mother and infant. Following informed consent, 2110 pregnant women will be randomised in a 1:1 ratio, with all study staff and participants masked to group allocation. Mother/infant pairs will be followed up for 12 months over six visits collecting clinical data on infections, antimicrobial use, safety and anthropometrics, in addition to nasopharyngeal, oropharyngeal, rectovaginal and vaginal swabs, maternal breastmilk and infant stool samples, in order to compare bacterial carriage, AMR rates and microbiome. Recruitment for Bulabula MaPei started in June 2019. Ethics and dissemination: This trial was approved and is being conducted according to the protocol approved by The Royal Children's Hospital Human Research Ethics Committee, Australia, and the Fiji National Health Research and Ethics Review Committee. The findings of this study will be disseminated in peer-reviewed journals and presented at conferences. Trial registration number: NCT03925480 .